The Role of Transthoracic Echocardiography in the Evaluation of Patients With Ischemic Stroke - Teodoro, Robson Sarmento [UNESP]; Silva, Gisele Sampaio; Modolo, Gabriel Pinheiro [UNESP]; Trivellato, Stella De Angelis [UNESP]; Souza, Juli Thomaz de [UNESP]; Luvizutto, Gustavo Jose; Carvalho Nunes, Helio Rubens de [UNESP]; Martin, Luis Cuadrado [UNESP]; Bazan, Rodrigo [UNESP]; Zanati Bazan, Silmeia Garcia [UNESP] (Frontiers Media Sa, 2021)
Background: Ischemic stroke can be classified into five etiological types, according to the Trial of Org 10172 in Acute Stroke Treatment (TOAST) classification, and its adequate investigation and characterization can aid in its clinical management and in preventing new events. Transthoracic echocardiography (TTE) plays a key role in investigating its etiology; approximately one-third of the patients remain without an adequate definition of the etiology or are classified as the undetermined TOAST type.
Objectives: To evaluate if the percentage of patients with indeterminate etiology according to the TOAST classification decreased after transthoracic echocardiography, to determine whether or not the prognosis after ischemic stroke is worse among patients classified as the undetermined TOAST type, and to verify the predictive capacity of echocardiography on the prognosis after ischemic stroke.
Methods: In this retrospective cohort study, clinical, neurological, and echocardiographic examinations were conducted when the patient was hospitalized for stroke. In-hospital mortality and functional capacity were evaluated at hospital discharge and 90 days thereafter. Multiple linear regression and multiple logistic regression models were adjusted for confounding factors. The level of significance was 5%.
Results: A total of 1,100 patients (men = 606; 55.09%), with a mean age of 68.1 +/- 13.3 years, were included in this study. Using TTE, 977 patients (88.82%) were evaluated and 448 patients (40.7%) were classified as the undetermined TOAST type. The patients who underwent TTE were 3.1 times less likely to classified as the undetermined TOAST type (OR = 0.32; p < 0.001). Echocardiography during hospitalization was a protective factor against poor prognosis, and reduced the odds of in-hospital death by 11.1 times (OR: 0.090; p < 0.001). However, the presence of the undetermined TOAST classification elevated the chance of mortality during hospitalization by 2.0 times (OR: 2.00; p = 0.013).
Conclusions: Echocardiography during hospitalization for ischemic stroke reduces the chances of an undetermined TOAST classification and the risk of in-hospital mortality. However, being classified as the undetermined TOAST type increases the chance of mortality during hospitalization, suggesting that evaluating patients using echocardiography during hospitalization for acute ischemic stroke is important.
Keywords: stroke; ischemic stroke; echocardiography; cardioembolism; stroke etiology